The Great Theft: Wrestling Islam from the Extremists by Khaled Abou El Fadl (New York: HarperSanFrancisco, 2005. 310 pages.) (American Journal of Islam and Society, 2005)
Written creeds, which always come much later than the original revelation,invariably seek to define theological “orthodoxy” over and against the perceivedheresies of competing sects. Thus, in Islam, the Fiqh Akbar I stoodagainst the Kharajites, the Wasiyat Abu Hanifah against the Qadarites andthe first Mu`tazilites, and the Fiqh Akbar II against the later Mu`tazilites.Later on, such theological treatises as al-Ash`ari’s Al-Ibanah and `Abd al-Qahir al-Baghdadi’s Kitab Usul al-Din appeared.In The Great Theft, Khaled Abou El Fadl revives this tradition by statingthat in the wake of numerous “acts of ugliness” committed by Muslims,the ummah has reached a grave theological crossroads. Muslims are nowdivided along a spectrum between two extremes. Fundamentally, this schismis one between “moderates” (the extreme being defined by those most willingto reinterpret the Islamic tradition in the light of contemporary realities)and “puritans,” who, on the basis of a selective reading of Islam’s strictestschool of law (Hanbali), claim that 90 percent of human affairs are alreadycovered by God’s law (the Shari`ah). At the heart of these diametricallyopposed worldviews, he claims, is a theological decision regarding creationand the Shari`ah’s meaning.Significantly, the book’s first part is devoted to an analysis of the presentcrisis. In the first chapter (“Islam Torn between Extremism andModeration”), Abou El Fadl describes the split that divides the Islamic communityand helpfully defines the terms moderate (as opposed to modernist,progressive, or reformist) and puritan (not fundamentalist, militant, extremist,radical, or jihadist). From the beginning, he lays aside the commonMuslim objections in the face of suicide bombings or beheadings: “the problemis with Muslims, not Islam per se.” Unfortunately, he argues, all sidesclaim that they are following the precepts of Islam. What is needed is a ...